2022
DOI: 10.1080/2331186x.2022.2109802
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and learning in age-homogeneous groups versus mixed-age groups in the preschool – the Swedish example

Abstract: The study presented in this article investigates how the curriculum is implemented and transformed by teachers in mixed-age and age-homogeneous groups, the most common age-constellations in the Swedish preschool. The data was collected through groups interviews with preschool teachers. The interviews were transcribed and analysed with the support of thematic analysis and connected to a sociocultural perspective on learning. The findings show that the teachers in the different age formations use both the same a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…The findings of the three-way mixed ANOVA indicated that children in K2 + K3 groups constructed conservation significantly better than children in K2 groups but not children in K3 groups. This result is partially consistent with the earlier research (Magnusson and Bäckman, 2022), which suggested that older children facilitated the learning of their younger peers in the mixedage group discussions, promoting younger children's higher-order thinking skills and cognitive development. In the meantime, this result partially corroborated the previous studies (White et al, 1976;Basargekar and Lillard, 2021), which argued that there was no difference between mixed-age groups and conventional groups in the conservation construction.…”
Section: How Do Children Construct Conservation Knowledge?supporting
confidence: 91%
“…The findings of the three-way mixed ANOVA indicated that children in K2 + K3 groups constructed conservation significantly better than children in K2 groups but not children in K3 groups. This result is partially consistent with the earlier research (Magnusson and Bäckman, 2022), which suggested that older children facilitated the learning of their younger peers in the mixedage group discussions, promoting younger children's higher-order thinking skills and cognitive development. In the meantime, this result partially corroborated the previous studies (White et al, 1976;Basargekar and Lillard, 2021), which argued that there was no difference between mixed-age groups and conventional groups in the conservation construction.…”
Section: How Do Children Construct Conservation Knowledge?supporting
confidence: 91%